An Informatics Tool for Water Resources Management in Shanghai City - Tao, Tao; Li, Shuping; Liu, Suiqing; Fu, Xiang (MTT, 2005)
The main subject of this paper is the water resources management informatics tool in use in Shanghai. Information-based capability is an important indicator of national strength, international competitiveness and degree of modernization. Information has become a strong new motive for the development of social productivity and progress in human civilization. Water information provides us with the technological foundation for transforming traditional water management practices into a modern system adhering to the principles of sustainable development. It is also an effective means for promoting the scientific management and working efficiency of water resources. This paper describes the data information management system used for urban water resources in Shanghai. Data management is at the core of an integrated water information management system. Water resources (surface water and groundwater)-Environment-Social-Economic constitute a complex system with many sub-systems that affect and depend on each other. Thus the volume of data in water resource information is very large, and the structure of the key elements and their relationship to each other are complicated, with more than 80% of the information relating to the geographical position of space distribution. Seeing that a lot of countries in the world use the advanced technology of geographical information systems (GIS), making for an enormous comprehensive benefit in managing water resources, we drafted a GIS platform, set up a data information system for urban water resources comprising a water resources development and management database, a water environmental management database, and an economic development and social development database.
Keywords: Ys; information tool; water resource; GIS; Shanghai